General mechanisms of coagulation and targets of anticoagulants (Section I). Position Paper of the ESC Working Group on Thrombosis--Task Force on Anticoagulants in Heart Disease. - De Caterina, R; Husted, S; Wallentin, L; Andreotti, F; Arnesen, H; Bachmann, F; Baigent, C; Huber, K; Jespersen, J; Kristensen, S; Lip, G; Morais, J; et al. (2013)
Contrary to previous models based on plasma, coagulation processes are currently believed to be mostly cell surface-based, including three overlapping phases: initiation, when tissue factor-expressing cells and microparticles are exposed to plasma; amplification, whereby small amounts of thrombin induce platelet activation and aggregation, and promote activation of factors (F)V, FVIII and FXI on platelet surfaces; and propagation, in which the Xase (tenase) and prothrombinase complexes are formed, producing a burst of thrombin and the cleavage of fibrinogen to fibrin. Thrombin exerts a number of additional biological actions, including platelet activation, amplification and self-inhibition of coagulation, clot stabilisation and anti-fibrinolysis, in processes occurring in the proximity of vessel injury, tightly regulated by a series of inhibitory mechanisms. "Classical" anticoagulants, including heparin and vitamin K antagonists, typically target multiple coagulation steps. A number of new anticoagulants, already developed or under development, target specific steps in the process, inhibiting a single coagulation factor or mimicking natural coagulation inhibitors.